Students’ Difficulties in Learning Reading Comprehension of Explanatory Text - Erlidawati; Rahayu, Rizka (Enlightenment Publishing, 2024)
Reading is the way in developing students’ comprehension of the written texts. The objective of reading is to know the main idea of reading to obtain and get the information involve content and the meaning from the text. In learning reading comprehension, the students faced many obstacles in comprehending the text. Cause of they have lack vocabulary and they do not know the meaning from the text. While they must learn various of text in learning reading. One of the texts that they must learn is explanatory text. Explanatory text explains about social, culture, scientific and other phenomena how and why something happen. It makes students’ bore in learning the reading, they assume that reading is difficult for them and they do not interest in learning reading comprehension. Some factors can influence students’ difficulties in learning reading comprehension like; the students are difficult to grasp the meaning from the text and they cannot different the sound of word that written and read. Then, they find the strange words when they read a text.